Up in the cloud: a case study of the industry evolution of cloud computing industry focused on Amazon Web Services - Uno, Matheus Kiyoshi Ramos (2022)
The thesis studies the industry evolution of the cloud computing industry with a focus on technology infrastructure. The study relies upon the major frameworks in the modern study of strategy, business models, and industry evolution. The concepts of competitive advantages as perceived by the competitive forces, the resource-based view, and the dynamic capabilities are utilized. These frameworks are contextualized in the cloud computing industry through the case study from 2006 until 2019 of Amazon Web Services—pioneer and top player of the IaaS cloud computing industry. The analysis indicates that cloud computing industry is in a fast progressive change trajectory. The industry is characterized by a consolidated market with intense competition driven by rapid technological advances. The thesis proceeds to analyze AWS’s strategy meticulously and understand how it was influenced by the recent market evolution.